Measuring and inferring the ice thickness distribution of four glaciers in the Tien Shan, Kyrgyzstan - Van Tricht, Lander; Huybrechts, Philippe; Van Breedam, Jonas; Fürst, Johannes; Rybak, Oleg; Satylkanov, Rysbek; Ermenbaiev, Bakyt; Popovnin, Victor; Neyns, Robbe; Paice, Chloë Marie; Malz, Philipp (Journal of Glaciology, 2021)
Glaciers in the Tien Shan mountains contribute considerably to the fresh water used for irrigation, households and energy supply in the dry lowland areas of Kyrgyzstan and its neighbouring countries. To date, reconstructions of the current ice volume and ice thickness distribution remain scarce, and accurate data are largely lacking at the local scale. Here, we present a detailed ice thickness distribution of Ashu-Tor, Bordu, Golubin and Kara-Batkak glaciers derived from radio-echo sounding measurements and modelling. All the ice thickness measurements are used to calibrate three individual models to estimate the ice thickness in inaccessible areas. A cross-validation between modelled and measured ice thickness for a subset of the data is performed to attribute a weight to every model and to assemble a final composite ice thickness distribution for every glacier. Results reveal the thickest ice on Ashu-Tor glacier with values up to 201 ± 12 m. The ice thickness measurements and distributions are also compared with estimates composed without the use of in situ data. These estimates approach the total ice volume well, but local ice thicknesses vary substantially.
CRIS-Team Scopus Importer:2021-04-02
Keywords: glacier volume; ice thickness measurements; Key words Glacier mapping; mountain glaciers; radio-echo sounding